ALGORITHMIC REALIZATION IMPACTS ASSESSMENT FOR RENEWABLE SOURCES ELECTRIC POWER ON RELIABILITY ELECTRICAL NETWORKS - Sobczuk, Dymitr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
For the effective operation of distributed energy sources and their use in complex electrical power networks, studies their properties, resulting from joint work in the electric power system. Algorithm of performance assessment regime provides reliability normal mode calculation. The calculations steady mode analyzes the significance of voltage levels at the nodes of the network and the deviation of active power losses in relation to the required value. Advanced analysis of daily schedules by using information obtained from automated system of commercial accounting of electric power.